Exploring the creep and oxidation behaviors of four types of FeCrAl alloys through small punch test at 600 °C: Experiments and simulations - Xiaowei Jiang; Jiawei Bai; Jinquan Guo; Huan Sheng Lai; Xianfeng Ma (Journal of Materials Research and Technology, 2023)
Four types of iron-chromium-aluminum (FeCrAl) alloys, composed of different elements, were used to investigate the creep performance and high-temperature oxidation resistance. The microstructures in the undeformed regions after the small punch creep test (SPCT) remained consistent with the as-received (AR) FeCrAl alloys, while the grain aspect ratio (GAR) decreased and grains elongated in the deformed regions. Amongst the four alloys, Q1 exhibited the worst oxidation resistance, whereas Q4 showed superior oxidation resistance due to the addition of Si. Precipitates were observed in the deformed regions after SPCT but not in undeformed regions, indicating that deformation had a positive effect on element segregation. Creep models including Norton power law, Monkman-Grant relationship, Larson-Miller Parameters, and Fracture-Time law were obtained. Calculation results from these creep models revealed that under low loads Q4 had lower minimum creep rate δm and longer creep fracture time tr compared to other alloys; however, Q3 demonstrated better performance in terms of δm and tr under high loads. This suggests a strong correlation between creep performance and loads. Additionally, finite element method (FEM) was employed to explore the effects of minor variation (±0.005 mm) in specimen thickness on SPT curves and SPCT curves. FEM results indicated that this slight variation alone did not account for discrepancies observed in load-deflection curves; deviations of ±6.1% for δm and ±6.3% for tr were found corresponding to specimens with 0.5 ± 0.005 mm thickness.